Intervention on The Role of Procurement Service Unit - Dharma, Haryo (JPAS (Journal of Public Administration Studies), 2018)
The purpose of this paper is to know more about the role of Procurement Service Unit in public procurement process in Indonesia and how government possibly intervene their decision because of their position as part of the government even though they should play a neutral position in the process. The establishment of this Procurement Services Unit actually is intended to be a mediator connecting users (government) with agents (providers/ suppliers). This research applied a qualitative content analysis approach. Data were collected through observation of secondary documents in January 2018. The research was conducted in Regional Office of Environmental Health and Disease Control Surabaya. The results show that the role of Procurement Service Unit needed to be expanded, not only just choosing the bidding winner but also take more control on procurement process. However, this unit already played the neutral position even though they were attached to the institution within their interventions, because of the introduction of e-procurement in Indonesia. But still, it can be argued because it is still need some approval from the actors itself, including the Procurement Service Unit, User, and the providers.